Afghanistan - Electronic Government Procurement Readiness Assessment and Roadmap - World Bank (Washington, DC, 2012)
The overriding objective of a national public procurement system is to deliver efficiency and value for money in the use of public funds, while adhering to fundamental principles of non- discrimination, equal treatment, and transparency. Procurement is therefore at the core of the Public Finance Management (PFM) system and contributes greatly to several of its objectives, including efficiency, transparency, and accountability. In respect of public procurement, the 2005 review of Afghanistan's PFM system identified a weak legal framework, lack of ownership, lack of capacity and the lack of a monitoring mechanism as the key issues in the area of procurement. Since then, following the recommendations of the PFM review report, the country has made substantial progress in improving its public procurement environment. The purpose of this report is to provide a roadmap which sets out the incremental steps which may be taken to introduce Electronic Government Procurement (E-GP) tools according to the speed and development of the reform agenda. The report will be disseminated to the stakeholders through a workshop, planned for July 2007. The workshop will discuss the challenges in implementation of an e-GP strategy both in terms of its components as well as the transition path to implementation.